Light bullets in transparent dielectrics. (1st March 2022) - Kandidov, V.P.; Zaloznaya, E.D.; Dormidonov, A.E.; Kompanets, V.O.; Chekalin, S.V.
Abstract: This paper presents a retrospective analysis of the development of notions in nonlinear optics: from beam self-focusing and pulse filamentation to light bullets – wave packets extremely compressed in space and time during laser light propagation in the bulk of a transparent medium. We describe the state of the art in studies of mid-IR light bullets in condensed media and air.